SOME REFLECTIONS ON MUQIMI - Karimova S. (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
The article provides information about the formation of Mukimi’s personality and work in the Kokan literary environment of the end of the 19th century and the beginning of the 20th century. Its place in the development of Uzbek literature is determined.